Ukraine national interests in Antarctica: the quantitative adjectives - Kuzko, O. V.; Savchenko, V. V.; Fedchuk, A. P. (Ukrainian Antarctic Journal, 2013)
At present the concept of national interests in Antarctic is not defined in any directive legislative act. Pursuant to this, the research is based on the assumption, that National interests of countries – Parties to the Antarctic Treaty (including Ukraine) lie in guaranteeing of universal values associated with Antarctica, which were systematized by the SCAR Social Science Action Group (SSAG) into the following six categories of multiple values: environmental, societal, economic, scientific, aesthetic, and political (with relevant subcategories in each value). Though the mentioned values have qualitative nature, their ranking and interpretation of received results is possible by means of mathematical apparatus. This study is devoted to determine the quantitative characteristics of importance of each Antarctic value using the judgement method that was effectually applied in politics by Prof. Thomas L. Saaty in the second half of XX century. The approach consists of three stages: 1) preparing the matrix with the list of the studied values, 2) filling the matrix elements by the experts’ judgements on the successive pairwise comparison of the values importance in accordance with ranks from 0 to 9, in compliance with the matrix consistency property (the matrix is consistent if aii =1 and aji =1/aij), and 3) task solution on the prepared matrix eigenvalues that give, after normalization, the comparative quantitative evaluations of the importance of each value. In the process of evaluation of national interests the following normative legal documents were used: State Special-Purpose Research Program in Antarctica for 2011-2020; decrees of the President; acts of the Cabinet of Ministers of Ukraine; and work and information papers of Ukraine presented for annual Antarctic Treaty Consultative Meetings starting from 2000. The following results of national interests’ expert judgment were obtained in the order of importance: scientific – 47,2%; political – 18,1%; economic – 15,2%; environmental – 10,5%; societal – 6,4%; aesthetic – 2,6%. The proposed method can be used for analysis of national interests of other states – Parties to the Antarctic Treaty. The received results serve as analytical basis for political decision-making by executive authorities concerning activity of Ukraine in Antarctica for near-term outlook and beyond, and also for substantiation of political position of Ukraine in appropriate bodies within the Antarctic Treaty System.